UJI PEMAKAIAN PUPUK CAIR URINE HEWAN PADA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI MAIN NURSERY - Leonardus Freddi Hutabarat; Sampoerno '; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Plant oil palm (Elaeis guineensis Jacq.) is a plantation crop which plays an important role for Indonesia as a mainstay commodity. Palm oil seedling is the planting of seedlings in a planting medium, so that the seeds are ready to be planted permanently in plantations. The research aim is to determine the effect of the use some liquid fertilizer animal urine on seedlings of oil palm (Elaeis guineensis Jacq.) and get the animal urine liquid fertilizer suitable for oil palm seedlings. Research was conducted at the Faculty of Agriculture, University of Riau, from January to April 2015. The study conducted using completely randomized design (CRD), which is consists of 5 treatments, each treatment was repeated 4 times to obtain 20 units of trial, as for the treatment given is a liquid fertilizer that consists of animal urine: sheep urine, goat urine, urine buffalo and cow urine. Data were analyzed using ANOVA and continued with further test Honestly Significant Difference (HSD) at 5 %. Research that has been carried out, showing that administration of liquid fertilizer urine of different animals on oil palm seedlings showed the real effect of the parameters as height of seedlings, the increase in diameter hump, increase the number of stem of leaves and root volume, while observations ratio crown roots and dry weight of seedlings show the effect is not real. Goat urine treatment showed the best results for all parameters of observation. Keywords: liquid fertilizer, oil palm, main nursery